Multimodal combination of neuroimaging methods for localizing the epileptogenic zone in MR-negative epilepsy - Říha, Pavel; Doležalová, Irena; Mareček, Radek; Lamoš, Martin; Bartoňová, Michaela; Kojan, Martin; Mikl, Michal; Gajdoš, Martin; Vojtíšek, Lubomír; Bartoň, Marek; Strýček, Ondřej; Pail, Martin; et al. (Scientific reports, 2022)
The objective was to determine the optimal combination of multimodal imaging methods (IMs) for localizing the epileptogenic zone (EZ) in patients with MR-negative drug-resistant epilepsy. Data from 25 patients with MR-negative focal epilepsy (age 30 ± 10 years, 16M/9F) who underwent surgical resection of the EZ and from 110 healthy controls (age 31 ± 9 years; 56M/54F) were used to evaluate IMs based on 3T MRI, FDG-PET, HD-EEG, and SPECT. Patients with successful outcomes and/or positive histological findings were evaluated. From 38 IMs calculated per patient, 13 methods were selected by evaluating the mutual similarity of the methods and the accuracy of the EZ localization. The best results in postsurgical patients for EZ localization were found for ictal/ interictal SPECT (SISCOM), FDG-PET, arterial spin labeling (ASL), functional regional homogeneity (ReHo), gray matter volume (GMV), cortical thickness, HD electrical source imaging (ESI-HD), amplitude of low-frequency fluctuation (ALFF), diffusion tensor imaging, and kurtosis imaging. Combining IMs provides the method with the most accurate EZ identification in MR-negative epilepsy. The PET, SISCOM, and selected MRI-post-processing techniques are useful for EZ localization for surgical tailoring.
Keywords: Young Adult; elektroencefalografie; neurozobrazování; Diffusion Tensor Imaging; Epilepsy; Electroencephalography; lidé; magnetická rezonanční tomografie; fluorodeoxyglukosa F18; Adult; Neuroimaging; Fluorodeoxyglucose F18; mladý dospělý; dospělí; Humans; epilepsie; Magnetic Resonance Imaging; zobrazování difuzních tenzorů